The moderating role of risk preference in advance value-added tax refund implementation - Siharini, Dwi; Sofyani, Hafiez (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This research is motivated by the limited studies on Value Added Tax (VAT) refund in advance. This study aims to examine the influence of the variables of ease of use, efficiency, and risk preference on the intention to implement VAT refund in advance and taxpayer compliance. This study also tests the role of risk preference as moderator.Design/Methodology/Approach: This research was conducted using a quantitative approach with an associative study design. The data used are primary data obtained from the distribution of questionnaires to respondents consisting of taxpayers in Yogyakarta, Indonesia. The present study also utilized Partial Least Squares Structural Equation Modelling (PLS-SEM) for data analysis. From the distribution of the questionnaire we obtained 102 taxpayers.Research findings: This study shows that ease of use and efficiency positively influence the intention of corporate taxpayers to carry out VAT refund in advance, while risk preference does not have a significant impact either as independent or moderating variable. Theoretical contribution/Originality: This study provides insights into the factors influencing taxpayers' interest in VAT refund in advance , such as ease, efficiency, and risk preference.Practitioner/Policy implication: This study highlights the need for the government and Yogyakarta Tax Office to simplify tax refund procedures, speed up tax refund processes, and ensure transparency to reduce taxpayer concerns. Research limitation/Implication: This research is limited to the taxpayer population located in the Yogyakarta region. Conditions and demographics in other regions may differ, so this research may not yet be able to depict the situation in those areas.